IMPLEMENTASI KEBIJAKAN E- PROCUREMENT PADA PENGADAAN BARANG/JASA DENGAN PRINSIP GOOD UNIVERISTY GOVERNANCE DI UNIVERSITAS TADULAKO - Mohamad Cahyadi; Muhammad Khairil; Intam Kurnia (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The objective of this research was to examine the implementation of e-Procurement in the procurement of goods/services with the principles of good university governance at Universitas Tadulako, guided by the Presidential Regulation Number 12 of 2021, which amends Presidential Regulation Number 16 of 2018 regarding Government Procurement of Goods/Services. E-Procurement in the procurement of goods/services with the principles of good university governance in this research refers to the process of e-Procurement in the procurement of goods and services. The analysis in this study utilized George C. Edward III's (1980) theory as cited in Widodo (2010) to assess four aspects influencing the effectiveness of policy implementation: Communication, Resources, Disposition/Attitude of Implementers, and Bureaucratic Structure.The research methodology employed in this study was qualitative research, a method used to investigate natural object conditions, where the researcher acts as the primary instrument. Data collection techniques involved triangulation (combined methods), data analysis was inductive, and the qualitative research findings emphasized meaning over generalizations. The results indicated that the implementation of e-Procurement in the procurement of goods/services with the principles of good university governance at Universitas Tadulako has not been effectively executed due to insufficient adherence to the principles in communication, resource allocation, disposition/attitude of implementers, and bureaucratic structure during implementation.